PENGHAYATAN TERHADAP KONSEP KETUHANAN PADA MASYARAKAT HINDU DI LOMBOK - Ningrat, Jro Ayu (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2019)
This paper is the result of research that aims to study the appreciation of the concept of divinity in Hindu societies in Lombok. This research was designed in a qualitative descriptive study to reveal the dimension of appreciation of the concept of divinity in Hinduism in Lombok. Based on the results of this study it was found that the implementation of religion in the midst of the life of the Hindu community in Lombok has similarities with the implementation of Hindu religion in Bali. The similarity is caused by several factors. First, Hindu societies in Lombok are migrants, most of whom migrated to Lombok after the Karangasem Kingdom arranged for social, cultural and religious life around the 16th century when there was an expansion of power to Lombok. Second, the reference sources used as guidelines for implementing religion by the Balinese in Lombok are almost the same as the reference sources used by their ancestors in Bali. Third, there is a policy from the royal government to implement a system in the form of a pasuara that is related to the implementation of Hinduism in Balinese communities in Lombok. Fourth, other factors that support, especially those related to the cultural adaptation of Balinese people with their new settlements in Lombok. The implementation of Hinduism in Lombok which uses the identity of the mention of the divine aspect with local dimensions is not released by the existence of divine concepts in the belief system of the Hindu community in Bali. With regard to that the existence of a divine identity that is not found in reference to the Vedic scriptures is a local wisdom that is used to appreciate the aspect of divinity so that the relationship between local Hindus and supernatural powers is closer. This is also based on the teachings conveyed by the Siwatattwa teaching that teach the dimension of divinity by giving a term that is very familiar with the life of the people of the archipelago. There is no belief in the aspect of divinity called local identity in relation to this matter in the scriptures. Vedas are not a mistake, but a truth that grows within Hindus on the basis of their respective beliefs. In line with that, it should not be a matter of difference in the mention of the name of God because of the nature of God that the versatile Brahman has many names according to the way Hindus live it. The most important thing in this context is that the implementation of Hinduism as implemented by the Balinese people in Lombok has essentially carried out the teachings of the Vedic scriptures that have been internally integrated with local culture.